Setting Cocoon Washing Parameters And Determining The Quality Indicators Of The Produced Raw Silk - Xaitova, Zumradxon Rakhmatullaevna; Mo’minova, Moxinur (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article studies the current state of cocoon washing equipment, the working process, mechanical cocoon washing machines and automatic cocoon washing machines. It is determined that the current technologies of raw silk production consist of four stages, namely, preparation, preparation, washing and control-collection. The development of specific recommendations for cocoon washing and the introduction of its technology are presented.